Formação de professores no contexto das propostas pedagógicas de Rudolf Steiner (pedagogia Waldorf), Maria Montessori e da experiência da Escola da Ponte - Santos, Evelaine Cruz dos [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The objective of this research was to investigate how is the process of training teachers who work in the context of educational proposals Waldorf, Montessori and the experience of the Ponte School(Bridge School), focusing on specific training courses for each of these proposals. Data were collected through the participation of the researcher as a student in training courses for each of the proposals in the periods 2009 to 2013, field work in schools that adopt the proposals referred to, conversations with teachers, seven interviews and a questionnaire, with teachers and /or trainers who work or have worked in these proposals. Data were recorded in an expanded field notes and interviews were audio-recorded and transcribed. The material was interpreted and discussed qualitatively, according to an interpretive ethnographic. This entire process was presented through narratives that revealed the lived experience of the researcher both in training courses as in schools and also made explicit discussions that occurs as the teacher training process to act on the three proposals, highlighting how the teaching of Mathematics It was approached these formations. A reflection on the themes that emerged was held. In the proposed, Waldorf highlight the theoretical-philosophical and methodological assumptions that underlie that are: self-knowledge (knowledge of self); the arts; and the class teacher (generalist teacher). In the method of Maria Montessori emphasize the theoretical-philosophical and methodological assumptions that underlie and its subsequent update, the importance of practice / training and self-knowledge. The experience of the Ponte School(Bridge School) excelled focused training in school (particularly the study circle). The research contributes to discussions for the training of teachers who teach Mathematics, pointing in particular to the inner teacher training through knowledge of himself, shed which is considered in the proposals ...

O objetivo desta pesquisa foi investigar como ocorre o processo de formação de professores para atuar no contexto das propostas pedagógicas Waldorf, Montessori e experiência da Escola da Ponte, com enfoque em cursos de formação para cada uma destas propostas. Os dados foram coletados através da participação da pesquisadora como aluna de cursos de formação para cada uma das propostas, ocorridos nos períodos de 2009 a 2013, trabalho de campo em escolas que adotam as propostas referidas, conversas com professores, sete entrevistas e um questionário, com professores e/ou formadores que atuam ou atuaram nestas propostas. Os dados foram registrados em notas de campo expandidas e as entrevistas foram gravadas em áudio e transcritas. O material foi interpretado e discutido de forma qualitativa, segundo um caráter etnográfico interpretativo. Todo esse processo foi apresentado através de narrativas que revelaram a experiência vivida pela pesquisadora tanto nos cursos de formação quanto nas escolas e, também, discussões que explicitaram como ocorre o processo de formação de professores para atuar nas três propostas, destacando como o ensino de Matemática foi abordado nestas formações. Foi realizada uma reflexão sobre os temas que emergiram. Na proposta Waldorf, destacamos os pressupostos teórico-filosófico-metodológicos que a embasam, o autoconhecimento (conhecimento de si mesmo), as artes e o professor de classe (professor generalista). No método de Maria Montessori salientamos os pressupostos teórico-filosófico-metodológicos que o embasam e sua consequente atualização, a importância da prática/estágio e o autoconhecimento. Na experiência da Escola da Ponte sobressaiu-se a formação centrada na escola (destaque para o círculo de estudos). A pesquisa contribui com discussões para a formação de professores que Ensinam Matemática, apontando, em especial, para a formação interior do professor através do...
Keywords: Escola da Ponte (Portugal); Professores - Formação; Waldorf, Metodo de educação; Montessori, Metodo de educação; Teachers, Training of